Heat treatment method for improving high-temperature strength of ZL201 aluminum alloy

By adopting new heat treatment processes in ZL201 aluminum alloy, including solid solution, quenching, low-temperature aging and high-temperature aging treatment, the problem of insufficient high-temperature strength of ZL201 aluminum alloy in the prior art has been solved, and the significant performance improvement of the alloy at high temperatures has been achieved.

CN119592891APending Publication Date: 2025-03-11NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411727038.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing heat treatment process of ZL201 aluminum alloy cannot effectively improve its high temperature strength, especially in high temperature environments, the thermal stability of the reinforced phase is insufficient, resulting in a decrease in the high temperature performance of the alloy.

Method used

A new heat treatment process is adopted, including four links: solid solution, quenching, low-temperature aging and high-temperature aging. Specific steps include screening alloy components, smelting and casting, solid solution treatment, low-temperature aging treatment and high-temperature aging treatment. The secondary precipitation of the T-phase with high thermal stability is promoted through high-temperature aging treatment, and the interface polarization effect is used to reduce the interface energy of the θ′-Al2Cu phase, thereby enhancing the thermal stability of the nano-strengthening phase.

Benefits of technology

The high temperature strength of ZL201 alloy was significantly improved, the tensile strength of 360℃ reached 130-150MPa, and the yield strength reached 105-125MPa, which was 16%-27% and 5%-15% higher than the T6 state.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592891A_ABST
    Figure CN119592891A_ABST
Patent Text Reader

Abstract

The invention discloses a heat treatment method for improving the high-temperature strength of ZL201 aluminum alloy, and belongs to the technical field of heat-resistant aluminum alloy materials. The heat treatment method specifically comprises the steps of solid solution, quenching, low-temperature aging and high-temperature aging. The microstructure of the alloy is regulated and controlled through the heat treatment process, nanometer strengthening phases (a rod-shaped T-Al20Cu2Mn3 phase and a needle-shaped theta '-Al2Cu phase) with high heat stability are successfully separated out, and the stable temperature of the T-Al20Cu2Mn3 phase reaches 350 DEG C. The high-temperature aging process can promote continuous precipitation of the T phase from the matrix, and Mn and Ti elements are segregated at the interface of the theta 'phase and the matrix, so that the thermal stability of the theta'-Al2Cu phase is improved. By the adoption of the heat treatment process, the tensile strength of the ZL201 aluminum alloy at 360 DEG C reaches 142 MPa, the yield strength of the ZL201 aluminum alloy at 360 DEG C reaches 121 MPa, and compared with a traditional T6 heat treatment process, the high-temperature tensile strength is improved by 27%, and the yield strength is improved by 15%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heat-resistant aluminum alloy materials, in particular to a heat treatment method for improving the high-temperature strength of a ZL201 aluminum alloy. Background Art

[0002] Al-Cu-Mn aluminum alloys have been widely used in aerospace, national defense and military fields due to their excellent mechanical properties and heat resistance, especially in the manufacture of high-temperature components, such as engine parts and fuselage structures. During service, traditional aluminum alloys are difficult to meet the requirements of high temperature and high pressure environments. Al-Cu-Mn aluminum alloys can provide excellent high-temperature oxidation resistance, resistance to plastic deformation (creep) and damage, and good thermal conductivity while ensuring lightweight. Common grades of this series of domestically produced heat-resistant aluminum alloys include ZL201, ZL204A and ZL205A.

[0003] ZL201 alloy exhibits excellent performance in high temperature applications. In the fields of aerospace, automobiles, etc., it can be used to manufacture structural parts in high temperature environments, such as turbine housings, cylinder heads, oil tank bottom shells, etc. The mechanical properties of ZL201 alloy depend to a large extent on the precipitation of nanoscale strengthening phases. The main strengthening phases in the alloy are θ'-Al2Cu phase and T-A1 20 Cu2Mn3 phase, due to the size difference between T phase and θ' phase (T phase is 80-2000nm long and 30-400nm thick; θ' phase is 10-50nm long and 1-5nm thick), according to the Hall-petch relationship, the smaller the grain size, the better the strengthening effect, so the previous heat treatment process mainly focuses on the optimization and research of θ' phase. The traditional T6 heat treatment process (solid solution + quenching + low temperature aging) can precipitate a large amount of dispersed θ' phase, thereby obtaining good room temperature strength. However, the thermal stability temperature of θ' phase is about 225℃. At high temperature, with the passage of time, the metastable θ′-Al2Cu phase will coarsen and transform into the equilibrium θ-Al2Cu phase. The coarsened θ′ or deformed θ particles reduce the effect of blocking dislocation movement, thereby deteriorating the high temperature strength of the alloy. However, the researchers found that the microstructure and mechanical properties of Al-Cu-Mn alloys can be improved after long-term thermal exposure at high temperature. Al-Cu-Mn-Zr-Sc alloys formed T-A1 after annealing at 300℃ / 3h 20Cu2Mn3 dispersed phase ensures the high yield strength of 280MPa of the alloy after aging at 300°C (Document 1N.A.Belov,ANAlabin,IAMatveeva, Optimization ofphase composition ofAl-Cu-Mn-Zr-Sc alloys for rolled products without requirement for solutiontreatment and quenching.J.Alloys Compd.583(2014), 206-213.). High temperature aging heat treatment of Al-Cu-Mn alloy can not only stimulate Mn to stabilize the metastable θ′ phase, but also promote the formation of T phase with high thermal stability. The precipitated T phase can make up for the strength loss of θ′ phase due to coarsening and transformation. Therefore, it is very necessary to explore the heat treatment process for T phase and give full play to the high temperature strengthening effect of T phase.

[0004] Microstructural thermal stability is a key factor to consider when designing heat treatment processes for high temperature applications. Improving the high temperature tolerance of Al-Cu-Mn alloys can be achieved by enhancing the main strengthening phases (θ′-Al2Cu phase, T-A1 20 Cu2Mn3 phase). In response to the problem of thermal stability of Al2Cu phase, studies have shown that the thermal stability of Al2Cu phase can be greatly improved by interface segregation. Sun Jun et al. used interface segregation to obtain a microstructure with excellent thermal stability in Al-Cu-Sc alloy, namely, fine dispersed dual precipitates, concentrated size distribution and strong Sc interface segregation at the θ′-Al2Cu / matrix interface. The Sc interface segregation not only ensures the thermal stability of θ′-Al2Cu by confining Cu inside the θ′-Al2Cu phase, but also prevents the potential θ′-Al2Cu dissolution from releasing Cu atoms to accelerate the coarsening of Al3Sc phase (Reference 2Y.H.Gao, C.Yang, JYZhang, LFCao, G.Liu, J.Sun&E.Ma(2019)Stabilizingnanoprecipitates in Al-Cu alloys for creep resistance at300℃,MaterialsResearch Letters,7:1,18-25.). Therefore, it is an effective measure to increase the service temperature of ZL201 aluminum alloy material to segregate "slow elements" at the interface through microalloying and appropriate heat treatment process, improve the thermal stability of Al2Cu phase, and inhibit the migration of precipitate phase / matrix interface.

[0005] The existing heat treatment scheme for ZL201 aluminum alloy is not applicable to high-temperature service conditions. It is of great significance for subsequent processing and application to formulate an effective heat treatment process to improve the thermal stability of the nano-reinforced phase in the grains of ZL201 aluminum alloy and adjust the number, size and distribution of the nano-reinforced phase in the organization to achieve the best mechanical properties of the alloy. Summary of the invention

[0006] The invention aims at the problems in the existing ZL201 alloy heat treatment strengthening technology and provides a heat treatment method for improving the high temperature strength of the ZL201 alloy. The heat treatment method can significantly improve the high temperature strength of the ZL201 alloy, the heat treatment process is simple and easy to implement, the cost is low, and it can be quickly popularized.

[0007] To achieve the above object, a heat treatment method for improving the high temperature strength of ZL201 alloy of the present invention comprises the following steps:

[0008] The first step is to select the alloy composition: ZL201 aluminum alloy material, the alloy element weight percentage expression is: Al a Cu b Mn c Ti d , where 93.35≤a≤94.75, 4.5≤b≤5.3, 0.6≤c≤1, 0.15≤d≤0.35, a+b+c+d=100;

[0009] The second step is alloy smelting and casting: according to the alloy composition, the materials are melted, refined and cast in sequence to obtain ZL201 aluminum alloy castings;

[0010] The third step is solution treatment: the ZL201 aluminum alloy casting is subjected to solution treatment;

[0011] Step 4: low temperature aging treatment: subjecting the solid solution ZL201 alloy obtained in step 3 to low temperature aging treatment;

[0012] Step 5: high temperature aging treatment: keep the low temperature aged ZL201 alloy obtained in step 4 at 250-300°C for 5-100 hours and air cool.

[0013] Preferably, in the second step, the materials are prepared according to the alloy components, and smelting, refining and casting are carried out in sequence to obtain ZL201 aluminum alloy castings. The specific steps are: pure aluminum, Al-Cu alloy, Al-Mn alloy and Al-Ti alloy are added into a resistance smelting furnace for smelting, and the temperature is raised to 720°C. After the aluminum ingot is melted, Al-Cu alloy, Al-Mn alloy and Al-Ti intermediate alloy are added, and the temperature is continued to be raised to 740-760°C, and the temperature is kept for 10-30 minutes until the alloy is completely melted. After uniform stirring, 1% C2Cl6 by mass of the melt is added for refining, and the alloy liquid is allowed to stand for 8-12 minutes. The alloy liquid is cast into a graphite mold at 300°C at 740°C to obtain ZL201 aluminum alloy castings.

[0014] Preferably, in the third step, the specific steps of the solid solution treatment are: keeping the ZL201 aluminum alloy casting at 525-548°C for 5-18 hours, taking it out and quenching it in 50-70°C water, and the quenching transfer time does not exceed 15s. After the solid solution treatment, there is no residual θ-Al2Cu phase at the grain boundary, and the Cu element is dissolved into the α-Al matrix to the maximum extent, obtaining a supersaturated α-Al solid solution phase.

[0015] Preferably, in the fourth step, the specific steps of low temperature aging treatment are: the solid solution ZL201 alloy obtained in the third step is kept at 170-180°C for 3-5 hours, air-cooled, and after low temperature aging treatment, the θ″-Al3Cu or θ′-Al2Cu phase is uniformly dispersed and precipitated in the matrix to reach the peak aging state of the Al2Cu phase. Among them, T-Al 20 The Cu2Mn3 phase is a black thick rod-like morphology with a length of 80-2500nm and a thickness of 30-500nm; the θ′-Al2Cu phase is a long needle-like morphology with a length of 10-50nm and a thickness of 1-5nm.

[0016] Preferably, in the fifth step, after high temperature aging treatment, T-A1 20 Cu2Mn3 phase precipitates in the matrix for the second time, and the θ″-Al3Cu phase transforms into the θ′-Al2Cu phase. Mn atoms are concentrated at the interface between the θ′-Al2Cu phase and the α-Al matrix, while Ti elements are concentrated in the θ′-Al2Cu phase, T-Al 20 The segregation of Cu2Mn3 phase at the interface with the matrix α-Al reduces the interfacial energy of the nanophase and inhibits the transformation of θ′-Al2Cu to θ-Al2Cu and the T-A1 20 The Cu2Mn3 phase is coarsened. A nano-strengthened phase with high thermal stability is obtained, among which T-Al 20 The Cu2Mn3 phase is a black thick rod-like morphology with a length of 80-2500nm and a thickness of 30-500nm; the θ′-Al2Cu phase is a long needle-like morphology with a length of 10-1200nm and a thickness of 5-60nm.

[0017] Preferably, the ZL201 alloy prepared by the heat treatment method has a tensile strength of 130-150 MPa at 360° C. and a yield strength of 105-125 MPa.

[0018] The present invention proposes a new heat treatment process for the traditional heat treatment mode of ZL201 alloy, including four steps: solid solution, quenching, low temperature aging and high temperature aging. Compared with the prior art, the heat treatment process of the present invention has the following significant advantages:

[0019] (1) High temperature aging treatment can promote the secondary precipitation of the highly thermally stable T phase, compensating for the strength loss caused by the coarsening and transformation of the θ′ phase after high temperature. In addition, the interface segregation effect reduces the interface energy of the θ′-Al2Cu phase and enhances the thermal stability of the nano-reinforced phase.

[0020] (2) By adopting the heat treatment process, a nano-strengthening phase with high thermal stability is obtained, that is, a large amount of dispersed T-Al 20 Cu2Mn3, θ′-Al2Cu phase. 20 The stable temperature of Cu2Mn3 phase reaches 350℃. The tensile strength of ZL201 alloy at 360℃ reaches 130-150MPa, and the yield strength reaches 105-125MPa. Compared with T6 state at 360℃, the tensile strength increases by 16%-27%, and the yield strength increases by 5%-15%.

[0021] (3) By using the heat treatment process, Mn atoms are segregated at the interface between the θ′-Al2Cu phase and the matrix α-Al, while Ti atoms are segregated at the interface between the θ′-Al2Cu phase and the T-Al1 20 The interface between Cu2Mn3 phase and matrix α-Al effectively inhibits the transformation of θ′-Al2Cu to θ-Al2Cu and the T-A1 20 Coarsening of Cu2Mn3 phase. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the heat treatment process diagram of ZL201 alloy.

[0023] Figure 2 This is the TEM image of the alloy obtained after the heat treatment process of T6+250℃ / 10h in Example 1. Among them, the black thick rod is T-A1 20 Cu2Mn3 phase; the long needle-shaped phase is θ′-Al2Cu phase.

[0024] Figure 3 This is the TEM-EDS display result of the alloy obtained after the heat treatment process of T6+250℃ / 10h in Example 1. DETAILED DESCRIPTION

[0025] In order to better understand the technical content of the present invention, specific embodiments are described below with reference to the accompanying drawings.

[0026] Figure 1 This is the heat treatment process flow chart of ZL201 alloy. First, the alloy composition is selected and smelted. The cast alloy is kept at 525-548℃ for 5-18 hours, taken out and quenched in 50-70℃ water, and the quenching transfer time does not exceed 15s. Then, it is kept at 170-180℃ for 3-5 hours, air-cooled, and subjected to low-temperature aging treatment. Then, it is kept at 250-300℃ for 5-100 hours, air-cooled, and subjected to high-temperature aging treatment to obtain ZL201 alloy with excellent high-temperature strength.

[0027] T-Al can be partially analyzed during the solution treatment process 20 Cu2Mn3 phase, in the subsequent quenching process, the cooling rate is too fast so that the remaining T phase cannot precipitate in time. In the low-temperature aging treatment, due to the low treatment temperature and short time, the effect on the T phase is small. However, during the high-temperature aging process, the intensification of atomic diffusion will promote the continued precipitation of the remaining T phase from the matrix. At the same time, during the high-temperature aging process, the Mn and Ti elements will be concentrated at the θ′ phase interface, which improves the thermal stability of the θ′-Al2Cu phase and obtains a microstructure with high thermal stability. Therefore, in order to further obtain a large amount of heat-resistant Al 20 Cu2Mn3 phase and thermally stable Al2Cu phase, for T6 state ZL201 alloy, subsequent heat treatment is carried out, and the heat treatment scheme is 250℃ / 5h~100h and 300℃ / 5h~100h, etc.

[0028] In the following examples, a KSL-1100X muffle furnace was used throughout the process to perform solution treatment, low-temperature aging treatment and high-temperature aging treatment on ZL201 alloy. The heating rate of the muffle furnace was 5°C / min, and the temperature control accuracy was ±1°C.

[0029] T6 described in the present invention refers to the heat treatment state of the air-cooled alloy after solution treatment (water cooling) + low-temperature aging treatment, and T5 refers to the heat treatment state of the air-cooled alloy after homogenization treatment + solution treatment (water cooling) + low-temperature aging treatment.

[0030] Example 1

[0031] (1) Alloy composition selection

[0032] The Al-Cu-Mn and Al-Cu-Ti ternary phase diagrams were calculated using Thermal-Calc software, and it was determined that α-Al+θ′-Al2Cu+T-A1 20 The alloy composition of Cu2Mn3 three-phase structure is Al 93.5 Cu 5.3 Mn 1.0Ti 0.2 (Weight percent).

[0033] (2) Selection of raw materials

[0034] The purity of each metal component selected for preparing the alloy ingot of the present invention is shown in Table 1. The alloy composition is Al 93.5 Cu 5.3 Mn 1.0 Ti 0.2 ;

[0035] Table 1 Purity of metal components used in preparing alloy ingots (wt.%)

[0036]

[0037] (3) Alloy smelting

[0038] Pure aluminum, Al-Cu alloy, Al-Mn alloy and Al-Ti alloy are added into a resistance melting furnace for smelting, and the temperature is raised to 720°C. After the aluminum ingot is melted, Al-Cu alloy, Al-Mn alloy and Al-Ti intermediate alloy are added, and the temperature is continued to rise to 740-760°C. The alloy is kept warm for 20 minutes until the alloy is completely melted. After uniform stirring, 1% C2Cl6 by mass of the melt is added for refining. The mixture is allowed to stand for 8 minutes. The alloy liquid is cast into a graphite mold at 300°C at 740°C to obtain a ZL201 aluminum alloy casting.

[0039] (4) Alloy heat treatment

[0040] The KSL-1100X muffle furnace was used to carry out solution treatment, low temperature aging treatment and high temperature aging treatment on ZL201 alloy castings. The heating rate of the muffle furnace was 5℃ / min, and the temperature control accuracy was ±1℃. The specific procedures are as follows:

[0041] a. Solution treatment: keep the alloy ingot at 536℃ for 12 hours, and then quench it in 60℃ water immediately after taking it out;

[0042] b. Low temperature aging treatment: keep the alloy ingot at 175℃ for 5 hours and air cool;

[0043] c. High temperature aging treatment: keep the alloy ingot at 250℃ for 10 hours and air cool.

[0044] (4) Organization and performance testing

[0045] The microstructure of the prepared material is Figure 2 As shown in the figure, a nano-strengthening phase with high thermal stability is obtained, namely, a large amount of dispersed T-Al 20 Cu2Mn3, θ′-Al2Cu phase, Figure 2 The black rod-like phase is T-A1 20Cu2Mn3 phase (length: 80-2500nm, thickness: 30-500nm, number density: 4.78×10 19 / m 3 , compared with the T6 state, the number density of the T phase increased by 78%), Figure 2 The medium-long needle-like phase is the θ′-Al2Cu phase (length: 10-1200nm, thickness: 5-60nm, number density: 0.23×10 21 / m 3 ).

[0046] The TEM-EDS results of the prepared materials are as follows Figure 3 As shown in the figure, Mn and Ti elements in ZL201 alloy are segregated at grain boundaries and θ′-Al2Cu phase interfaces after high temperature aging heat treatment.

[0047] The results of mechanical properties test show that after the T6 state ZL201 alloy is heat treated at 250℃ / 10h, the tensile strength at 360℃ reaches 142MPa, which is 27% higher than that of the T6 state; the yield strength reaches 121MPa, which is 15% higher than that of the T6 state.

[0048] Example 2

[0049] The other processes are the same as in Example 1, except that the high temperature aging treatment is 250°C / 25h+air cooling, and a nano-strengthening phase with high thermal stability is obtained, i.e., a large amount of dispersed T-Al 20 Cu2Mn3, θ′-Al2Cu phase.

[0050] The results of mechanical properties test show that after the ZL201 alloy is heat treated at T6+250℃ / 25h, the tensile strength at 360℃ reaches 137MPa, which is 22% higher than that of the T6 heat treated state, and the yield strength reaches 115MPa, which is 10% higher than that of the T6 heat treated state.

[0051] Example 3

[0052] The other processes are the same as in Example 1, except that the high temperature aging treatment is 250°C / 50h+air cooling, and a nano-strengthening phase with high thermal stability is obtained, i.e., a large amount of dispersed T-Al 20 Cu2Mn3, θ′-Al2Cu phase.

[0053] The results of mechanical properties test show that after the ZL201 alloy is heat treated at T6+250℃ / 50h, the tensile strength at 360℃ reaches 134MPa, which is 20% higher than that of the T6 heat treated state.

[0054] Example 4

[0055] The other processes are the same as in Example 1, except that the high temperature aging treatment is 250°C / 100h+air cooling, and a nano-strengthening phase with high thermal stability is obtained, i.e., a large amount of dispersed T-Al 20 Cu2Mn3, θ′-Al2Cu phase.

[0056] The results of mechanical properties test show that after the ZL201 alloy is heat treated at T6+250℃ / 100h, the tensile strength at 360℃ reaches 125MPa, which is 12% higher than that of the T6 heat treated state.

[0057] Example 5

[0058] The other processes are the same as in Example 1, except that the high temperature aging treatment is 300°C / 5h+air cooling, and a nano-strengthening phase with high thermal stability is obtained, i.e., a large amount of dispersed T-Al 20 Cu2Mn3, θ′-Al2Cu phase.

[0059] The results of mechanical properties test show that after the ZL201 alloy is heat treated at T6+300℃ / 5h, the tensile strength at 360℃ reaches 138MPa, which is 23% higher than that of the T6 heat treated state.

[0060] Example 6

[0061] The other processes are the same as in Example 1, except that the high temperature aging treatment is 300°C / 10h+air cooling, and a nano-strengthening phase with high thermal stability is obtained, i.e., a large amount of dispersed T-Al 20 Cu2Mn3, θ′-Al2Cu phase. Among them, T-Al 20 Cu2Mn3 phase length: 80-2500nm (mean 370nm), thickness: 30-500nm (mean 132nm), number density: 3.10×10 19 / m 3 Compared with the T6 state, the number density of the T phase increased by 15%. The θ-Al2Cu phase has a long needle-like morphology, with a length of 10-1200nm (average 387nm), a thickness of 5-60nm (average 16nm), and a number density of 0.12×10 21 / m 3 .

[0062] The results of mechanical properties test show that after the ZL201 alloy is heat treated at T6+300℃ / 10h, the tensile strength at 360℃ reaches 130MPa, which is 16% higher than that of the T6 heat treated state.

[0063] Example 7

[0064] The other processes are the same as in Example 1, except that the high temperature aging treatment is 300°C / 25h+air cooling, and a nano-strengthening phase with high thermal stability is obtained, i.e., a large amount of dispersed T-Al 20 Cu2Mn3, θ′-Al2Cu phase.

[0065] The results of mechanical properties test show that after the ZL201 alloy is heat treated at T6+300℃ / 25h, the tensile strength at 360℃ reaches 129MPa, which is 15% higher than that of the T6 heat treated state.

[0066] Comparative Example

[0067] The other processes are the same as steps (1) to (3) of Example 1, except that in the heat treatment process (T5), the ZL201 alloy casting is first kept at 530°C for 8 hours, then heated to 540°C and kept for 8 hours, immediately taken out and quenched directly into 60°C water, then kept at 175°C for 5 hours, and air-cooled.

[0068] The results of mechanical property tests show that the tensile strength at 300°C is 118MPa, the yield strength is 74MPa, and the elongation is 7%.

[0069] The distribution of length, thickness and number density of T phase and θ′ phase after different heat treatment processes are shown in Table 2.

[0070] The heat treatment processes and high temperature mechanical properties of all the above embodiments are compared with those of the comparative examples, as shown in Table 3.

[0071] Table 2 Distribution of length, thickness and number density of T phase and θ′ phase after different heat treatment processes

[0072]

[0073] Table 3 Heat treatment process and high temperature mechanical properties in the examples and comparative examples

[0074]

Claims

1. A heat treatment method for improving the high temperature strength of ZL201 alloy, characterized in that: The following steps are involved: The first step is to select the alloy composition: ZL201 aluminum alloy material, the alloy element weight percentage expression is: Al a Cu b Mn c Ti d , where 93.35≤a≤94.75, 4.5≤b≤5.3, 0.6≤c≤1, 0.15≤d≤0.35, a+b+c+d=100; The second step is alloy smelting and casting: according to the alloy composition, the materials are melted, refined and cast in sequence to obtain ZL201 aluminum alloy castings; The third step is solution treatment: the ZL201 aluminum alloy casting is subjected to solution treatment; Step 4: low temperature aging treatment: subjecting the solid solution ZL201 alloy obtained in step 3 to low temperature aging treatment; Step 5: high temperature aging treatment: keep the low temperature aged ZL201 alloy obtained in step 4 at 250-300°C for 5-100 hours and air cool.

2. The method according to claim 1, characterized in that In the second step, the materials are prepared according to the alloy components, and smelting, refining and casting are carried out in sequence to obtain ZL201 aluminum alloy castings. The specific steps are: pure aluminum, Al-Cu alloy, Al-Mn alloy and Al-Ti alloy are added into a resistance smelting furnace for smelting, and the temperature is raised to 720°C. After the aluminum ingot is melted, the Al-Cu alloy, Al-Mn alloy and Al-Ti master alloy are added, and the temperature is continued to be raised to 740-760°C, and the temperature is kept for 10-30 minutes until the alloy is completely melted. After uniform stirring, 1% C2Cl6 by mass of the melt is added for refining, and the mixture is allowed to stand for 8-12 minutes. The alloy liquid is cast into a graphite mold at 300°C at 740°C to obtain ZL201 aluminum alloy castings.

3. The method according to claim 1, characterized in that In the third step, the specific steps of solution treatment are: keep the ZL201 aluminum alloy casting at 525-548°C for 5-18 hours, take it out and quench it in 50-70°C water, and the quenching transfer time does not exceed 15s.

4. The method according to claim 1, characterized in that In the fourth step, the specific steps of low temperature aging treatment are: keeping the solid solution ZL201 alloy obtained in the third step at 170-180°C for 3-5 hours and air cooling.

5. The method according to any one of claims 1 to 4, characterized in that: The prepared ZL201 alloy has a tensile strength of 130-150 MPa at 360°C and a yield strength of 105-125 MPa.